2017
DOI: 10.2458/v24i1.20971
|View full text |Cite
|
Sign up to set email alerts
|

How can traditional livelihoods find a place in contemporary conservation politics debates in India? Understanding community perspectives in Sundarban, West Bengal

Abstract: We document the economic and socio-cultural vulnerability of a forest-dependent community inhabiting the forest fringe island of Satjelia in the Indian Sundarban. Using simple artisanal methods, they have practiced traditional livelihoods like fishing and collecting wild honey from the forests for more than a century. Despite having established cultural integrity and traditional occupations, this group is not indigenous, and are therefore treated as 'others' and 'settlers.' An ethnographic study describes thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…A more definitive answer might be provided for the question whether valuation will reduce inequalities and redistribute power. As we have described for BRT, and as a number of authors have shown elsewhere, tiger conservation has tended to increase inequalities and deprivation through the legal notification of inviolate tiger reserves that prevent any form of development activity within them (Bijoy 2011;Rai et al 2018;Sen and Pattnaik 2017;Taghioff and Menon 2010). The Verma Report (2015) does not outline an approach to reduce these inequalities and all indications are that the flow of investments for conservation resulting from the monetization of services might increase inequality through curtailing access to services for local people and through the physical displacement of people from tiger reserves as required by law.…”
Section: Why Value a Tiger Reserve?mentioning
confidence: 87%
“…A more definitive answer might be provided for the question whether valuation will reduce inequalities and redistribute power. As we have described for BRT, and as a number of authors have shown elsewhere, tiger conservation has tended to increase inequalities and deprivation through the legal notification of inviolate tiger reserves that prevent any form of development activity within them (Bijoy 2011;Rai et al 2018;Sen and Pattnaik 2017;Taghioff and Menon 2010). The Verma Report (2015) does not outline an approach to reduce these inequalities and all indications are that the flow of investments for conservation resulting from the monetization of services might increase inequality through curtailing access to services for local people and through the physical displacement of people from tiger reserves as required by law.…”
Section: Why Value a Tiger Reserve?mentioning
confidence: 87%
“…These people are referred to as 'forest workers'. Forest workers constitute a class of marginalized people who are landless and are entirely dependent on the forest resources to subsist (Sen and Pattanaik 2017a). 19 However, people like the agriculturalists and land labourers, who are not regular forest workers, also depend on the forest resources in varying degree to supplement their income during lean seasons.…”
Section: 3 Context Of the Field And Methodologymentioning
confidence: 99%
“…Other than that, it is also mentioned that how issues of resource access and governance are framed, negotiated, and addressed. Author Amrita Sen write down in her research paper on the economic and socio-cultural vulnerability of a forestdependent community who is the inhabitant of the Satjelia Island in Sundarban [6] . Author mainly done her research study based on PA management (Protected Area).…”
Section: Literature Reviewmentioning
confidence: 99%